The mitochondrial tricarboxylate carrier: unexpected increased activity in starved silver eels - ZARA, Vincenzo; GIUDETTI, Anna Maria; FERRAMOSCA, Alessandra; CAPOBIANCO, Loredana; Palmieri L; Gnoni GV (Biochemical and Biophysical Research Communications, 2000)
The tricarboxylate carrier was purified to homogeneity from liver mitochondria of European eel at the silver and the yellow stage and functionally reconstituted into liposomes. Unexpectedly, the molecular activity of the tricarboxylate carrier obtained from silver eel was about twofold higher than that of the same protein from yellow eel, although eels at the silver stage stop feeding. Parallel changes were found in the activities of the lipogenic enzymes in silver eels. This suggests a functional coordination between all these proteins sequentially involved in hepatic lipogenesis. Cardiolipin added to proteoliposomes strongly stimulated the activity of the purified tricarboxylate carrier from yellow eels, whereas it slightly reduced the activity of the same protein from silver eels. The higher activity of the tricarboxylate carrier from silver eels could therefore be ascribed, at least in part, to a different composition of the lipid domain surrounding the carrier protein, possibly in response to the hormonal alterations accompanying metamorphosis from yellow to silver stage.